Camping and hiking - Champion, Neil. (New York : Powerkids Press, 2011)
Provides an overview of hiking and camping, with information on equipment, safety, setting up camp, avoiding hiking hazards, being prepared, and other related topics.
Includes bibliographical references (p. 31) and index.
6.5
5-8.
5-8
Keywords: Camping -- Juvenile literature; Hiking -- Juvenile literature; Camping; Hiking; Camping; Hiking